On the optimal timing of switching from non-renewable to renewable resources: dirty vs clean energy sources and the relative efficiency of generators - Elettra Agliardi; Luigi Sereno (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
We develop a model on the optimal timing of switching from non-renewable to renewable energy sources with endogenous extraction choices under emission taxes and abatement costs. We assume that non-renewable resources are "dirty" inputs and create environmental degradation, while renewable resources are more environmentally friendly, although they may be more or less productive than the exhaustible resources. The value of the switching option from non-renewable to renewable resources is characterized. Numerical applications show that an increase in emission taxes, abatement costs or demand elasticity slows down the adoption of substitutable renewable resources, while an increase in the natural rate of resource regeneration, the stock of renewable resources or the relative productivity parameter speeds up the investment in the green technology.
Keywords: D81; H23; Q28; Q38; Q40; Q50; 330